TARGETING DNA METHYLATION ON TRANSGENERATIONAL CONSEQUENCES OF PRENATAL STRESS-INDUCED DEPRESSION - Nia Kurnianingsih (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background: Depression is a common mental disorder with disabilities and mortalities burden. Maternal stress during pregnancy has a strong correlation with the depression of children event in their adulthood phase. Abundant maternal cortisol transfer to the fetus generates blunted hypothalamus-pituitary-adrenal axis response. Objective: To understand the mechanism of targeting DNA methylation on transgenerational consequences of prenatal stress-induced depression. Methods: This review provides a comprehensive explanation of the DNA methylation changes as well as the occasion of new potential therapy that focused on DNA methylation inhibitors in depression from 33 trusted sources. Results: Higher fetal circulation of cortisol led to epigenetic changes during fetal development in an antenatal stress situation. DNA methylation of crucial genes such as brain-derived neurotrophic factor (BDNF) and nuclear receptor subfamily 3 group C member 1 (NR3C1) are responsible for the molecular mechanism of depression progression into the next generation through transcriptional inhibition. Conclusion: Demethylation is becoming a potential target to reduce the risk of depression in children who has a risk of prenatal stress mother. The role of plant bioactive compound as demethylation agent is promising and need further exploration. Keywords: depression, DNA methylation, prenatal stress.